Equality - Patel, Mars; Prabhakar, Samaira; Scott, Nahalia (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2019)
The grade 3/4 and grade 7 class at Ross Drive Public School worked together to learn about treaties, Shannen Koostachin, and Shannen’s Dream. The students were asked to think about what a safe and comfy education might look like and why it is unfair that Shannen Koostachin had to fight for this right. To learn more, visit www.shannensdream.ca.